2011
DOI: 10.1261/rna.2808411
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal proteins' association with transcription sites peaks at tRNA genes in Schizosaccharomyces pombe

Abstract: Ribosomal proteins (RPs) are essential components of ribosomes, but several RPs are also present at transcription sites of eukaryotic chromosomes. Here, we report a genome-wide ChIP-on-chip analysis of the association of three representative 60S RPs with sites in the Schizosaccharomyces pombe chromosomes. All three proteins tend to bind at the same subset of coding and noncoding loci. The data demonstrate selective RNA-dependent interactions between RPs and many transcription sites and suggest that the RPs bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 56 publications
(73 reference statements)
2
19
0
Order By: Relevance
“…These observations suggest the presence of ribosomal subunits at these sites. This may even be a general feature of eukaryotes since several RPs associate with nascent transcripts also in budding and fission yeast (Schroder and Moore 2005;De and Brogna 2010;De et al 2011). The Drosophila study also reported rapid incorporation of radioactive amino acids at the chromosomes and nucleolus in polytenic nuclei (Brogna et al 2002).…”
Section: Introductionmentioning
confidence: 85%
“…These observations suggest the presence of ribosomal subunits at these sites. This may even be a general feature of eukaryotes since several RPs associate with nascent transcripts also in budding and fission yeast (Schroder and Moore 2005;De and Brogna 2010;De et al 2011). The Drosophila study also reported rapid incorporation of radioactive amino acids at the chromosomes and nucleolus in polytenic nuclei (Brogna et al 2002).…”
Section: Introductionmentioning
confidence: 85%
“…Interestingly, RNAPIII genes (tRNA and 5SRNA) found throughout the genome are known to cluster at the centromere and associate with condensin in the presence of a specific threshold level of transcription (Iwasaki et al 2010). Ribosomal proteins (RpLs), specifically RpL7, RpL11, and RpL25 associate with centromeric tRNA clusters; unlike RpL association at euchromatic loci, the centromeric association is sensitive to RNaseA and RNaseT1 treatments, indicating the RNA involved is single stranded (De et al 2011). While the purpose of ribosomal protein recruitment to these areas is unknown, De et al (2011) speculate a role for RpLs in centromere function, possibly through an association with nascent centromere transcripts (Choi et al 2011).…”
Section: Boundary Elementsmentioning
confidence: 99%
“…Ribosomal proteins (RpLs), specifically RpL7, RpL11, and RpL25 associate with centromeric tRNA clusters; unlike RpL association at euchromatic loci, the centromeric association is sensitive to RNaseA and RNaseT1 treatments, indicating the RNA involved is single stranded (De et al 2011). While the purpose of ribosomal protein recruitment to these areas is unknown, De et al (2011) speculate a role for RpLs in centromere function, possibly through an association with nascent centromere transcripts (Choi et al 2011). tRNAs may not be the only type of barrier sequence between pericentric and centromeric regions.…”
Section: Boundary Elementsmentioning
confidence: 99%
“…The degree of change varied greatly for different proteins and showed that ribosomal proteins were highly expressed and either incorporated into ribosomal subunits or rapidly degraded Lam et al, 2007). It is also intriguing that ribosomal protein complexes associate with chromosomes and in particular transcription start sites of tRNAs, although the nature of these complexes and their function are as yet unknown (De et al, 2011).…”
Section: Protein Composition Of the Nucleolusmentioning
confidence: 99%